1992
DOI: 10.1063/1.106991
|View full text |Cite
|
Sign up to set email alerts
|

Use of tertiarybutylarsine in atomic layer epitaxy and laser-assisted atomic layer epitaxy of device quality GaAs

Abstract: The use of trimethylgallium (TMGa) and tertiarybutylarsine (TBAs) in atomic layer epitaxy (ALE) and laser-assisted atomic layer epitaxy (LALE) of GaAs is studied for the first time. TBAs is found to be a direct and suitable replacement for arsine (AsH3) in achieving monolayer self-limiting growth. Carbon contamination in the GaAs films grown by LALE using TMGa and TBAs is greatly reduced relative to those using TMGa and AsH3. Laser structures single GaAs quantum wells grown by ALE and LALE using TBAs exhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The processes have not been very successful, and in many cases use of very high temperatures or plasma or laser assistance has been required. Interesting results have been obtained with t -butylarsine at temperatures near 400 °C or more though. , Conclusion on the earlier III−V ALD studies is not straightforward since all the papers are strictly focused on epitaxy. However, we believe that the dehalosilylation chemistry may open up a new era in III−V ALD chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The processes have not been very successful, and in many cases use of very high temperatures or plasma or laser assistance has been required. Interesting results have been obtained with t -butylarsine at temperatures near 400 °C or more though. , Conclusion on the earlier III−V ALD studies is not straightforward since all the papers are strictly focused on epitaxy. However, we believe that the dehalosilylation chemistry may open up a new era in III−V ALD chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Nevertheless, a very limited number of LALD studies have, at present, been reported in the literature. [16] NH 3 and BBr 3 are two precursors that have previously been used for ALD and CVD of BN. [6,14] It is well known that photo-dissociation of NH 3 using an ArF excimer laser, which operates at 193 nm, produces NH and NH 2 .…”
Section: Introductionmentioning
confidence: 99%